STUDY KINERJA KOMODITAS KELAPA SAWIT DI KALIMANTAN TIMUR - Fatah, Abdul (Universitas 17 Agustus 1945 Samarinda, 2013)
Oil palm development has been recognized in the province of East Kalimantan very rapidly in recent decades. Although nationwide, Indonesia has been known as a the world's largest producer of crude palm oil, but its productivity is still very low when compared to Malaysia. By considering the availability of land and favorable climate, Indonesia remains a great opportunity to increase the productivity of oil palm. Moreover, with the government policies continue to be improved (including vision 36:25), it is expected to accelerate the development of upstream and downstream sectors of the oil palm. This study aims to determine the achievement level of productivity of oil palm in East Kalimantan Province and positioning these achievements at regional and national level. Research carried out for about five months in the province of East Kalimantan. This study is a combination of a literature review with observations directly to the field. The data collected were analyzed descriptively, then compared the achievements of East Kalimantan against other provinces in Kalimantan and Sumetera, and look at the performance of East Kalimantan oil palm on national level. The results revealed that the total area of oil palm plantations in East Kalimantan by July 2013 has reached 1,002,284 hectares, with a production of 6,538,743 tonnes of FFB and CPO 1,438,523 tons, as well as the productivity of 13.24 tonnes FFB/ha/year and CPO yield 21.70%. Position of oil palm performance achievements of East Kalimantan province on Kalimantan regional level for the planting area still under the Central Kalimantan province and West Kalimantan. For CPO yield performance still under West Kalimantan but above the South Kalimantan. Compared to Sumetera, achievements palm plantation acreage is still below the three provinces, but already above the other seven provinces. For CPO yield performance, still under the three provinces in Sumetera. Position of oil palm acreage achievement on national level accounted for about 7.56% of the total area of oil palm plantations nationwide, but in term of performance for productivity is still far below the national vision.